Snapshot of Nurse Readiness for the Covid-19 Pandemic in Indonesia: A Qualitative Study - Kholis, Anja Hesnia; Hidayah, Nurul; Priyanti, Ratna Puji; Asri, .; Kurdi, Fahruddin; Hidayat, Wahyu; Sarbani, .; Arianti, . (KnE Life Sciences, 2021)
During the Covid-19 pandemic, nurses who served as frontline healthcare providers are experiencing issues with extreme workload demand and under-provision of protective resources. This study aims to understand nurse readiness for the Covid-19 pandemic in Indonesia. The study uses a qualitative phenomenology approach with purposive sampling. Participants were recruited from the regional hospital in East Java, Indonesia. The criteria of participants were nurses who worked face-to-face with Covid-19 patients from various wards. The total sample size is 20 participants. In-depth interviews were conducted to gather the data, which was analyzed using Colaizzi’s phenomenological method. Five themes emerged: (1) fear of getting infected; (2) PPE adequacy supply; (3) unclear patient distribution flow; (4) nurse supporting ecosystem; (5) education and training in infectious diseases. The evaluation of nurses’ readiness concerned their knowledge, the supply of safety equipment, and support from various ecosystems. Nurses were concerned about various elements including catching the disease themselves, adjusting to the environment and new work procedures, physical discomfort due to special protective equipment, witnessing the suffering and death of patients, and long-term separation from family members. They need an integrated support system to help them fighting Covid-19. Attention from fellow nurses who help each other in crises, family support, and institution support are the support systems that determine the readiness of nurses. Keywords: covid-19, nurse readiness, pandemic, qualitative study